Positive Psychology in Multicultural Mathematics Education: Perspectives of Prospective Mathematics Education Teachers - Loviana, Selvi; Agustina, Rina; Sinaga, Risma Margaretha (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This study explores prospective mathematics teachers' perceptions of the importance of positive psychology and cultural diversity in mathematics learning within multicultural classrooms. A qualitative approach with a case study design was employed. The participants were fifteen prospective mathematics teachers from various regions, selected using purposive sampling. Data were collected through semi-structured interviews and open-ended questionnaires and then analyzed using thematic analysis. This study was conducted in April 2025 at the State Islamic University (UIN) Jurai Siwo Lampung. The data were analyzed using thematic analysis as developed by Braun and Clarke (2006). The findings reveal that most prospective teachers are initially aware of positive psychology's role in creating a supportive learning environment, including using praise, encouraging positive emotions, and developing students' potential. In addition, they view cultural diversity as a valuable aspect that can enrich the learning process, although their understanding remains general and is not yet reflected in concrete instructional planning. These findings highlight the need to integrate positive psychology and multicultural education into teacher education curricula to equip future teachers with inclusive and culturally responsive pedagogical competencies. This study also provides a foundation for developing training programs that prepare prospective teachers to manage multicultural classrooms effectively.